A High Precision Fiber Bragg Grating Inclination Sensor for Slope Monitoring. (24th June 2019) - Xu, Hongbin; Li, Feng; Zhao, Weigang; Wang, Shupeng; Du, Yanliang; Bian, Ce
Abstract : A high precision and small size Fiber Bragg Grating (FBG) inclination sensor which is used for slope monitoring is proposed in this paper. The FBG inclination sensor has a pendulum structure for high precision and a circular body for easy installation in the common inclinometer pipe. The sensitivity of the FBG inclination sensor can reach 400 pm/deg by optimizing its parameters. The test results show the superior performance of this FBG inclination sensor in terms of static characteristics, and its sensitivity is 406.6 pm/deg. The comparison experiment shows the static characteristics of the FBG inclination sensor are better than the traditional electrical inclination sensor.